The effect of mouthrinses containing zinc and triclosan on plaque accumulation, development of gingivitis and formation of calculus in a 28-week clinical test - Schaeken, M J; Van der Hoeven, J S; Saxton, C A; Cummins, D (Journal of clinical periodontology, 1996)
Experimental mouthrinses containing 0.4% zinc sulphate and 0.15% triclosan, which differed in base formulations were compared to a commercially available non-active control mouthrinse. Following baseline clinical examinations for plaque, gingival bleeding and calculus, the volunteers were provided with a dental prophylaxis and given oral hygiene instruction, stratified into 3 groups and given 1 of 3 mouthrinses. Further clinical assessments were performed after 4, 16 and 28 weeks. Salivary mutans streptococci were also monitored during the study. At 4 weeks, plaque and calculus scores in all groups were low compared to baseline. During the remainder of the study, these improvements were not maintained and both plaque and calculus levels increased in all groups. Plaque was significantly lower (P < 0.05) than in the control at all time points. Calculus was significantly lower (P < 0.05) than in the control at all time points. Calculus was significantly lower at week 28 for experimental mouthrinse group 2. Gingival bleeding also decreased in the initial 4 weeks but increased thereafter in the control group. In contrast, gingival bleeding was significantly (P < 0.05) lower in the two experimental groups than in the control group. No significant changes in mutans streptococci were observed.